The Impact of Recruitment Strategies and Crew Competencies on Maritime Operational Performance: A Study of PT Sillo Maritime Perdana Tbk - Baruno Winahyu Aji; Syahdan Tanjung; April Gunawan Malau; Agung Kwartama (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The maritime sector is critical for global trade and economic development, yet challenges in workforce development persist, particularly in tanker operations handling dry bulk cargo like agricultural products. This research investigates the interplay between recruitment strategies, crew competencies, and ship operational performance, with a focus on PT Sillo Maritime Perdana Tbk, a key player in Indonesia’s offshore shipping sector. Addressing gaps in aligning workforce development with industry demands, this study explores the effectiveness of recruitment practices and competency development within the operational context of this organization. This study aimed to evaluate the influence of recruitment strategies and crew work competencies, individually and collectively, on improving operational performance at PT Sillo Maritime Perdana Tbk. Using a mixed-methods approach, the research employed Statistical Equation Modeling (SEM) to analyze quantitative data from 117 participants and conducted thematic analysis of qualitative insights from experts, lecturers, graduates, and head workers. The results revealed that recruitment strategies and crew competencies significantly contribute to operational performance, with a combined positive effect observed. Structured recruitment and ongoing skill development tailored to industry demands were identified as critical. The findings also highlighted the transformative role of educational technology in bridging the gap between academic training and operational realities. The study provides actionable insights for PT Sillo Maritime Perdana Tbk and similar organizations, emphasizing the need for collaborative efforts to enhance workforce readiness, operational efficiency, and sustainability in maritime activities.